Synthesis and characterization of a magnetically separable CoFe2O4/TiO2nanocomposite for the photomineralization of formic acid - Paruchai Pongwan (2018)
A CoFe 2 O 4 /TiO 2 nanocomposite was successfully synthesized by coupling the modified sol-gel with hydrothermal techniques. The obtained CoFe 2 O 4 /TiO 2 nanocomposite was characterized by X-ray diffraction for phase composition and crystallinity. TEM images revealed that the shape of the as prepared samples was almost spherical and the average particle sizes were found to be in the range of 5-35 nm. The saturation magnetization (M s ) of CoFe 2 O 4 /TiO 2 nanocomposite was determined to be 29.64 emu g -1 . Photocatalytic activity and cycle stability were studied by the photomineralization of formic acid under solar light irradiation. © 2013 Copyright Taylor and Francis Group, LLC.